Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Transformasional Terhadap Kinerja Karyawan Dimediasi Oleh Komitmen Afektif ( Studi Pada Karyawan PT. Asaputex Jaya Tegal ) - Itsna Noor Rahmawati; Intan Ratnawati (JURNAL ILMIAH EDUNOMIKA, 2023)
Telework practices as a result of COVID-19 have changed the way employees work, especially related to Employee Performance. This study aims to determine, analyze and test the effect of telework on employee performance through mediation of work-life balance and technostress during the COVID-19 pandemic. This study adopted a quantitative approach with 115 respondents, and used the SmartPLS 3.0 application to help process data using the SEM-PLS analysis technique. The results of the study show that Work-Life Balance does not have a significant mediating effect on the relationship between Telework and Employee Performance during the COVID-19 Pandemic. Keywords : Telework, Work-life balance, Technostress, Employee performance